2007
DOI: 10.1128/jcm.01922-06
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Study of Antibiotic Resistances and Their Relevant Genes in Korean Avian Pathogenic Escherichia coli Isolates

Abstract: Antibiograms and relevant genotypes of Korean avian pathogenic Escherichia coli (APEC) isolates (n ‫؍‬ 101) recovered between 1985 and 2005 were assessed via disc diffusion test, PCR, restriction enzyme analysis, and sequencing. These isolates were highly resistant to tetracycline (84.2%), streptomycin (84.2%), enrofloxacin (71.3%), and ampicillin (67.3%), and most of the tetracycline, streptomycin, enrofloxacin, and ampicillin resistances were associated with tetA and/or tetB, aadA and/or strA-strB, mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
36
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 34 publications
12
36
2
1
Order By: Relevance
“…Class 1 and/or 2 integrons have been reported in clinical isolates of E. coli (Solberg et al, 2006), resistant coliforms from human and animal sources (Van Essen-Zanderbergen et al, 2007), non-coliform pathogenic bacteria (Chang et al, 2007), E. coli from human stools (Phongpaichit et al, 2008), bacteria from food (Sunde, 2005), avian pathogenic E. coli strains (Kim et al, 2007) and also in aquatic environments (Roe et al, 2003). Together, class 1 and 2 integrons accounted for 17 (13%) of 130 multidrug-resistant coliform isolates in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Class 1 and/or 2 integrons have been reported in clinical isolates of E. coli (Solberg et al, 2006), resistant coliforms from human and animal sources (Van Essen-Zanderbergen et al, 2007), non-coliform pathogenic bacteria (Chang et al, 2007), E. coli from human stools (Phongpaichit et al, 2008), bacteria from food (Sunde, 2005), avian pathogenic E. coli strains (Kim et al, 2007) and also in aquatic environments (Roe et al, 2003). Together, class 1 and 2 integrons accounted for 17 (13%) of 130 multidrug-resistant coliform isolates in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Apparently resistance mechanisms or a considerable number of antibiotic resistance genes were located outside the integrons either on chromosomes or plasmids [6], therefore, not all the resistance profile of the isolates could be explained by the expression of the gene cassettes found within the integrons [24]. Nevertheless, some isolates carrying integrons were susceptible to the corresponding antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the potentially pathogenic E. coli isolates examined in this study were resistant to uncommon antibiotics, such as cefazolin, gentamicin, and ciprofloxacin, used in veterinary treatments (18). It has also been reported that E. coli from healthy humans in eight developing countries were resistant to these new generation antibiotics (16). Based on these results, we suggest that the Korean government should attempt to curtail the use of these antibiotics for agricultural production in order to prevent the dissemination of resistance genes that may eventually reduce the effectiveness of important antibiotics.…”
Section: Genomic Similarity and Population Structure Of Expec Strainsmentioning
confidence: 96%
“…The occurrence of antibiotic resistant pathogenic E. coli varies by animal host (13). While Kim et al (16) reported significant increases in the prevalence of antibiotic resistant avian pathogenic E. coli from 2000 to 2005, the occurrence and patterns of antibiotic resistant pathogenic E. coli from other animal and human sources in South Korea have yet to be reported.…”
mentioning
confidence: 98%